Analisis Minat Beli Konsumen E-Commerce Shopee Selama Masa Pandemi Covid-19: Studi pada Konsumen di Kota Bandung, Indonesia - Ilham Nur Ramadan (International Journal Administration, Business & Organization, 2021)
Buying interest is how likely consumers buy a brand and services or how likely consumers switch from one brand to another brand. Consumer buying interest is crucial in buying interest due to a company because interest in buying is done step that consumers before planning to buy a product. The phenomenon of this research is about how much buying interest of Shopee E-Commerce consumers during the covid-19 pandemic around Bandung. The research method is using quantitative descriptive to describe a phenomenon, event, symptom, and incident that occurs factually, systematically, and accurately. Quantitative research methods are used on the data obtained from the results of the questionnaire answers that have been distributed and carried out to analyze data in the form of numbers and calculations using statistical methods. The sample used was 112 Shopee E-Commerce consumers around the City of Bandung at random, data testing was carried out including validity, reliability, and descriptive tests using a formula based on average. The results of the descriptive study reveal that the buying interest of Shopee E-Commerce consumers during the covid-19 pandemic around Bandung City was appertain high.